PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUAN MASYARAKAT MENGGUNAKAN MEDIA VIDEO DAN LEAFLET DALAM UPAYA PENCEGAHAN DEMAM BERDARAH DENGUE DI DESA WANGISAGARA KABUPATEN BANDUNG - Ruhyat, Ejeb; Firdaus, Rayhan; Tamara, Metha Dwi (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
Dengue fever is an infectious disease has been an increase in the spread. According to the West Java Health Office, the number of DHF patients in West Java in early 2024 was 24,540 cases, with 199 deaths. This is due to the occurrence of Extraordinary Events of DHF in several districts / cities. One of the villages in Bandung Regency, precisely in the working area of the Wangisagara Health Center, the number of DHF cases in 2024 from January to April was 22 cases, Wangisagara Village was the village with the highest number of DHF cases among the other 2 villages. Counseling with audio-visual media (video) has an impact in increasing knowledge of dengue prevention. The purpose of this study was to determine the effect of health education using video and leaflet media in an effort to prevent the incidence of Dengue Fever in Wangisagara Village, Bandung Regency. This research method uses a quantitative method with a type of quasy experiment research with a pre-post test two group design approach. With a population of 150 respondents with a sample of 60 respondents in two neighbourhood. The results showed a p-value of 0.000 (<0.05), this value indicates that there is an influence before and after being given education with video and leafleat. The conclusion is that there is an effect of health education using video and leaflet media in an effort to prevent the incidence of Dengue Fever.